(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Based on the government regulation of the republic of Indonesia no 72 of 2005 concerning article 15, the village government is obliged to manage village potential in order to achieve the objectives of laying authority in the implementation of village autonomy, these objectives include improving people’s welfare, equity and justice, democracy and respect for culture local, paying attention to the potential and diversity of the region. The aim of the research is to describe the role of the village government in the development of mahangetang island tourism object. The focus of the research in the study is on four aspects, namely : 1). (attraction), 2) (accessibility), 3). (facility), 4) (institutional. Keyword : Role of village government, tourism.